ESA's Planetary Science Archive: Preserve and present reliable scientific data sets. (January 2018) - Besse, S.; Vallat, C.; Barthelemy, M.; Coia, D.; Costa, M.; De Marchi, G.; Fraga, D.; Grotheer, E.; Heather, D.; Lim, T.; Martinez, S.; Arviset, C.; et al.
Abstract: The European Space Agency (ESA) Planetary Science Archive (PSA) is undergoing a significant refactoring of all its components to improve the services provided to the scientific community and the public. The PSA supports ESA's missions exploring the Solar System by archiving scientific peer-reviewed observations as well as engineering data sets. This includes the Giotto, SMART-1, Huygens, Venus Express, Mars Express, Rosetta, Exomars 2016, Exomars RSP, BepiColombo, and JUICE missions. The PSA is offering a newly designed graphical user interface which is simultaneously meant to maximize the interaction with scientific observations and also minimise the efforts needed to download these scientific observations. The PSA still offers the same services as before (i.e., FTP, documentation, helpdesk, etc.). In addition, it will support the two formats of the Planetary Data System (i.e., PDS3 and PDS4), as well as providing new ways for searching the data products with specific metadata and geometrical parameters. As well as enhanced services, the PSA will also provide new services to improve the visualisation of data products and scientific content (e.g., spectra, etc.). Together with improved access to the spacecraft engineering data sets, the PSA will provide easier access to scientific data products that will help to maximize the science return of ESA's space missions. Highlights: The PSA has changed his interface to improve science accessibility and discovery through ESA missions. The PSA hosts close to 50 TB of data with almost 10 millions products. The development of the PSA will provide a full multi-mission -instrument archive with geometrical and GIS capabilities. Science ready products from comets, asteroids and planets are available for free.